Gardens as Science Learning Contexts Across Educational Stages: Learning Assessment Based on Students’ Graphic Representations - Eugenio-Gozalbo, Marcia; Aragón, Lourdes; Ortega-Cubero, Inés (Frontiers in Psychology, 2020)
The educational use of daily-life contexts is considered a valuable strategy to promote meaningful science learning, since it facilitates the establishment of connections between previous knowledge, personal interests, and new learning. The aim of this work is to provide evidence to support the presence of gardens at educational centers, by assessing key science topics whose learning is promoted at the pre-school, primary, secondary, and university stages. To this end, we analyzed the paired graphic representations of “a garden” that students drew both before and after their participation in a garden-based learning program. Firstly, we obtained the frequency of appearance of every represented element, and afterwards characterized the level of change between paired graphic representations. Sample size was of 24-19-25-29 pairs per stage, respectively. Across all stages, an overall improvement in students’ graphic expression was observed, which can be attributed to their experience in the space. At the pre-school stage, the garden favored the establishment of some simple cause-effect relationships which were consolidated at the primary stage, and provided a climate of motivation and affectivity that was evident in the final drawings, given the enormous quantity of details represented, the level of the finished product, and the careful combination and variety of colors. The presence of elements related to water notably increased in final graphic representations from pre-school, primary, and secondary education, thus evidencing that the use of gardens facilitates an approach to responsible water management. At the university stage, students initially demonstrated good knowledge of conventional agriculture, while the gardening experience -which was based on permaculture practices- helped evolve their ideas towards an alternative model of cultivation. The most prevalent science learning across all stages was related to plant knowledge, particularly to their anatomical traits and diversity. Finally, the role of educational gardens as models for students was evidenced, which suggests the importance of teachers and institutions carefully considering which model to offer. Overall, our results support the legitimacy of incorporating gardens to educational centers, particularly for promoting contact with live plants and plant knowledge, and potentially for promoting contact with garden fauna and activities oriented towards learning about it.